Asteraceae ïº©ïºïºïº³ïº” ïº‘ïº¸ïº®ïº“ - ï»›ïº®ï»³ï»¢ ï»§ïº¼ïº®ï·², ïºïº³ïº®ïºØ¡; ïº£ï»¤ï»´ïºª ï»£ïº ï»´ïºª, ï»ï»“ïºŽØ¡ (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
ïº” ï»Ÿïº´ïº˜ïº” ïºï»§ï»®ïºï»‰ ï»£ï»¦ ïºï»Ÿï»ŒïºŽïº‹ï» ïº” ïºï»Ÿï»¤ïº®ï»›ïº’ïº” ØŒïºïº« ïº©ïºïº³ïº– ïº§ï»¼ï»³ïºŽ ïºï»Ÿïº’ïº¸ïº®ïº“ ïºï»»ï»‹ïº˜ï»´ïºŽïº©ï»³ïº” ïº—ï»¨ïºŽï»ï»Ÿïº– ïºï»Ÿïºªïºïºïº³ïº” ïºï»Ÿïº¤ïºŽï»Ÿï»´ïº” ïº§ïº¼ïºŽïº‹ïºº ïº‘ïº¸ïº®ïº“ ïºï»Ÿï»®ïºï»— ï»ïºï»Ÿï»¤ï»Œï»˜ïºªïºïº• ïºï»Ÿïºœï»ïº®ï»³ïº” ï»“ï»² ï»«ïº¬ï»© ïºï»»ïºŸïº°ïºØ¡ ï»ï»Ÿï»®ïº£ï»ˆïº– ïºï»Ÿï»”ïº®ï»ï»—ïºŽïº• ï»“ï»² ïºïº‘ï»ŒïºŽïº© ïº§ï»¼ï»³ïºŽ ïºï»Ÿïº’ïº¸ïº®ïº“ ïºï»»ï»‹ïº˜ï»´ïºŽïº©ï»³ïº” ï»ïºïº·ï»œïºŽï» ïºŸïºªïºïºï»§ï»¬ïºŽ ïºï»Ÿï»¤ï»¤ïºŽïº³ï»´ïº” ïºï»Ÿïºªïºïº§ï» ï»´ïº” ï»ïºï»Ÿïº¨ïºŽïºïºŸï»´ïº” ØŒï»›ï»¤ïºŽ ï»Ÿï»®ïº£ï»ˆïº– ïºï»Ÿïº˜ï»ïºŽï»³ïº®ïºïº• ï»“ï»² ïºï»Ÿï»¤ï»Œï»˜ïºªïºïº• ïºï»Ÿïºœï»ïº®ï»³ïº”  ï»£ï»¦ ïº£ï»´ïºš ïºïº‘ï»ŒïºŽïº©ï»«ïºŽ ï»ïºï»§ï»®ïºï»‹ï»¬ïºŽ ï»ïº—ïº®ïº©ïº©ï»«ïºŽ ï»‹ï» ï»° ïº³ï»„ïº¤ï»² ïºï»Ÿï»®ïºï»—ïº” .